Forward-time population genetics simulations : methods, implementation, and applications. - Peng, Bo, 1974- (John Wiley & Sons, 2012)
The only book available in the area of forward-time population genetics simulations-applicable to both biomedical and evolutionary studies The rapid increase of the power of personal computers has led to the use of serious forward-time simulation programs in genetic studies. Forward-Time Population Genetics Simulations presents both new and commonly used methods, and introduces simuPOP, a powerful and flexible new program that can be used to simulate arbitrary evolutionary processes with unique features like customized chromosome types, arbitrary nonrandom mating schemes, virtual subpopulati.